THE COMBINATION OF EXTERNAL RADIATION THERAPY WITH HIGH DOSE RATE BRAHYTERAPY BOOST FOR PROSTATE CANCER: A COMPARATIVE CHARACTERISTIC OF TWO FRACTION MODES - S. V. Kanaev; S. N. Novikov; G. I. Gafton; R. V. Novikov (Сибирский онкологический журнал)
The purpose of the study was to analyze treatment outcomes in prostate cancer patients, who received external radiotherapy combined with high dose rate (HDR) 198Ir brachytherapy boost of 10 Gy in 2 fractions or 15 Gy in 1 fraction. Material and methods. Between July 2012 and June 2017, 98 patients with prostate cancer received radiation therapy at N.N. Petrov National Medical Research Center of Oncology (St-Petersburg, Russia). Intensitymodulated radiation therapy (IMRT) at a total dose of 46–50 Gy was delivered to the prostate, seminal vesicles and regional lymph outflow areas (RTOG, 2009). The patients were then divided into 2 groups. Group I patients (81 patients, 82.7 %) received HDR brachytherpy boost of 10 Gy in 2 fractions, Group II patients (17 patients, 17.3 %) received HDR brachytherpy boost of 15 Gy in 1 fraction. Inclusion criteria were: high or extremely high risk of relapse according to NCCN (2010), no evidence of distant metastases and no evidence of pronounced urinary tract disorders (residual urine volume less than 50 ml, IPSS less than 17 points, maximum urination rate ≥10 ml / sec). Assessment of radiation-induced complications (toxicity) was carried out in accordance with generally accepted RTOG / EORTC (1995) criteria and taking into account the terminological recommendations of CTCAE v 4.0 (2009). Results. The median follow-up time was 39.2 [30.7; 48.7] (20.3–69.8) months in Group I and 37.0 [30.9; 47.9] (23.7–50.7) months in Group II. The 3-year disease-free survival rate in the study groups regardless of the boost was 77.1 % (75.9 % in Group I and 77.8 % in group II, p=0.7). The 3-year disease-free survival rates in patients with high and extremely high risk regardless of the radiotherapy regimen were 88.6 % and 70.8 %, respectively (р=0.04). Genitourinary early radiation toxicity and rectal intestinal early radiation toxicity of grade 3 were observed in 13.5% and 12.3 % of Group I patients and in 17.6 and 5.9 % of Group II patients. The most significant late complications were the formation of urethral stricture (1 patient of group I) and postradiation rectal stenosis (1 patient of group II). Evaluation of the level of erectile function in both groups showed a significant decrease in satisfaction with the quality of sexual life, which, apparently, can be explained not only by radiation damage to the structures responsible for hemodynamics of the penis, but also by castration syndrome due to prolonged hormonal deprivation in the vast majority of patients. Conclusion. The combination of external beam radiation therapy with HDR brachytherapy boost is an effective method of radical treatment of prostate cancer patients with high and extremely high risk of recurrence.